Impaired cerebral blood flow regulation and cognition in male football players. (17th July 2021) - Marley, Christopher J.; Owens, Thomas S.; Tsukamoto, Hayato; Stacey, Benjamin S.; Corkill, Robin; Bailey, Damian M.
Abstract : Football players are at increased risk of neurodegeneration, the likely consequence of repetitive mechanical trauma caused by heading the ball. However, to what extent a history of heading the ball affects cerebral blood flow (CBF) regulation and its potential relationship to cognitive impairment is unknown. To address this, we recruited 16 concussion‐free male amateur football players (age: 25 ± 6 y) with a history of heading the ball (18 ± 6 y) and 18 sex, age, education, and activity‐matched controls with no prior history of contact sport participation or concussion. Cerebral perfusion was measured at rest and in response to both hyper/hypocapnia to determine cerebrovascular reactivity to carbon dioxide (CVRCO2HYPER/HYPO ) using transcranial Doppler ultrasound and capnography, with the sum reflecting the cerebral vasomotor range. Cognition and visuomotor coordination were assessed using the Montreal cognitive assessment (MoCA) and the Grooved Pegboard Dexterity Test (GPD), respectively. While no differences in cerebral perfusion were observed ( p  = 0.938), CVRCO2HYPER/HYPO ( p  = 0.038/ p  = 0.025), cerebral vasomotor range ( p  = 0.002), MoCA ( p  = 0.027), and GPD performance (dominant hand, P  ≤ 0.001) were consistently lower in the players compared to controls. These findings are the first to demonstrate that CBF regulation and cognition are collectively impaired in male football players with history of heading the ball, which may contribute to neurodegeneration.